The civil liability of the legal person for damages to human and fundamental rights (2022)
The strengthening of civil justice in Latin American states can lead to greater success in determining the civil liabilities of economic actors in the event of direct violation, participation, or complicity in violations of human and fundamental rights. This document aims to show that in the face of the gaps and deficiencies civil justice has shown for victims at the international, supranational, and extraterritorial levels, the State civil jurisdiction can offer suitable legal tools so that victims have access to justice and comprehensive compensation for material and non-material damages that may be generated in the activity of private state and multinational companies.